Anti-malarial Activities of Two Actinomycete Isolates from Sabah Soil Involved Inhibition of Glycogen Synthase Kinase 3? - Dhiana Efani Dahari; Raifana Mohamad Salleh; Fauze Mahmud; Lee Ping Chin; Noor Embi; Hasidah Mohd Sidek (Tropical Life Sciences Research, 2016)
Exploiting natural resources for bioactive compounds is an attractive drug discovery strategy in search for new anti-malarial drugs with novel modes of action. Initial screening efforts in our laboratory revealed two preparations of soil-derived actinomycetes (H11809 and FH025) with potent anti-malarial activities. Both crude extracts showed glycogen synthase kinase 3? (GSK3?)-inhibitory activities in a yeast-based kinase assay. We have previously shown that the GSK3 inhibitor, lithium chloride (LiCl), was able to suppress parasitaemia development in a rodent model of malarial infection. The present study aims to evaluate whether anti-malarial activities of H11809 and FH025 involve the inhibition of GSK3?. The acetone crude extracts of H11809 and FH025 each exerted strong inhibition on the growth of Plasmodium falciparum 3D7 in vitro with 50% inhibitory concentration (IC50) values of 0.57 ± 0.09 and 1.28 ± 0.11 ?g/mL, respectively. The tested extracts exhibited Selectivity Index (SI) values exceeding 10 for the 3D7 strain. Both H11809 and FH025 showed dosage-dependent chemo-suppressive activities in vivo and improved animal survivability compared to non-treated infected mice. Western analysis revealed increased phosphorylation of serine (Ser 9) GSK3? (by 6.79 to 6.83-fold) in liver samples from infected mice treated with H11809 or FH025 compared to samples from non-infected or non-treated infected mice. A compound already identified in H11809 (data not shown), dibutyl phthalate (DBP) showed active anti-plasmodial activity against 3D7 (IC50 4.87 ± 1.26 ?g/mL which is equivalent to 17.50 ?M) and good chemo-suppressive activity in vivo (60.80% chemo-suppression at 300 mg/kg body weight [bw] dosage). DBP administration also resulted in increased phosphorylation of Ser 9 GSK3? compared to controls. Findings from the present study demonstrate that the potent anti-malarial activities of H11809 and FH025 were mediated via inhibition of host GSK3?. In addition, our study suggests that DBP is in part the bioactive component contributing to the anti-malarial activity displayed by H11809 acting through the inhibition of GSK3?. Pengeksploitasian sebatian bioaktif daripada sumber semula jadi merupakan strategi menarik dalam usaha pencarian drug anti-malaria baru dengan mod tindakan novel. Usaha penyaringan awal di makmal kami telah menemukan dua persediaan aktinomiset tanah (H11809 dan FH025) dengan aktiviti anti-malaria. Kedua-dua ekstrak kasar menunjukkan ciri anti-glikogen sintase kinase 3? (anti-GSK3?) menggunakan sistem pengasaian berasas-yis. Kajian terdahulu telah menunjukkan perencat GSK3, litium klorida (LiCl), berupaya menindas pertumbuhan parasitaemia dalam model infeksi malaria roden. Kajian ini dijalankan untuk menentukan sama ada aktiviti anti-malaria H11809 dan FH025 melibatkan perencatan GSK3?. Kedua-dua ekstrak aseton H11809 dan FH025 menunjukkan perencatan yang baik terhadap pertumbuhan Plasmodium falciparum 3D7 secara in vitro, dengan nilai kepekatan perencatan 50% (IC50) 0.57 ± 0.09 dan 1.28 ± 0.11 ?g/mL, masing-masing. Ekstrak yang diuji turut bersifat memilih bagi 3D7 dengan nilai indeks pemilihan melebihi 10. Secara in vivo, ekstrak H11809 dan FH025 menunjukkan aktiviti kemo-penekanan berkadaran-dos dan meningkatkan kemandirian mencit berbanding mencit terinfeksi tanpa perlakuan. Analisis Western menunjukkan peningkatan (6.79 hingga 6.83 kali ganda) terhadap pemfosfatan serin (Ser 9) GSK3? dalam sampel hepar mencit terinfeksi dengan perlakuan ekstrak H11809 atau FH025 berbanding sampel daripada mencit tidak terinfeksi atau mencit terinfeksi tanpa perlakuan. Sebatian bioaktif yang telah dikenal pasti dalam H11809 (data tidak ditunjukkan), iaitu dibutil ftalat (DBP) menunjukkan aktiviti anti-plasmodium yang baik terhadap parasit strain 3D7 (IC50 4.87 ± 1.26 ?g/mL bersamaan 17.50 ?M) serta aktiviti kemo-penekanan in vivo yang baik (kemo-penekanan 60.80% pada dos 300 mg/kg berat tubuh [bt]). Pemberian DBP turut menyebabkan peningkatan pemfosfatan Ser 9 GSK3? hepar berbanding kawalan. Penemuan daripada kajian ini menunjukkan aktiviti anti-malaria H11809 dan FH025 diperantara melalui perencatan GSK3? hos. Tambahan lagi, kajian ini mencadangkan DBP sebagai satu komponen bioaktif yang menyumbang kepada aktiviti anti-malaria H11809 melalui perencatan GSK3?.